Togo: Politics, economy and society in 2005 - Dirk Kohnert (Africa Yearbook Volume 2: Politics, Economy and Society South of the Sahara in 2005, 2006)
When the longest-serving African dictator, Gnassingbé Eyadéma, died unexpectedly in February after 38 years of autocratic rule, political conflict flared up again. His son, Faure Gnassingbé sized power in a coup with the backing of the army and the Barons of the ruling party. Violent protest at home and diplomatic pressure of major donors and African peers forced Gnassingbé to hold presidential elections in April. But as the elections were rigged right from the beginning, it was no surprise that they confirmed the power of the incumbent as heir to the throne of his father. In the interest of political stability in the sub-region, neighbouring states, France and the ECOWAS condoned the election results and the brutal political persecution of opponents. About 700 people died and some 40,000 fled to neighbouring Benin and Ghana in fear of reprisals. This, as well as the continuing suspension of aid from the EU, contributed to the further deterioration of the economy. – – Als Gnassingbé Eyadéma, der am längsten amtierende afrikanische Diktator, im Februar nach 38 Jahren autokratischer Herrschaft unerwartet starb, flammten die politischen Konflikte erneut auf. Sein Sohn Faure Gnassingbé hatte mit Unterstützung der Armee und der Barone der Regierungspartei durch einen Putsch die Macht an sich gerissen. Heftige Proteste im eigenen Land und diplomatischer Druck wichtiger Geldgeber und afrikanischer Partner zwangen Gnassingbé im April, Präsidentschaftswahlen abzuhalten. Da die Wahlen jedoch von Anfang an manipuliert waren, war es keine Überraschung, dass sie die Macht des Amtsinhabers als Thronfolger seines Vaters bestätigten. Im Interesse der politischen Stabilität in der Subregion duldeten die Nachbarstaaten, Frankreich und die ECOWAS das Wahlergebnis und die brutale politische Verfolgung von Gegnern. Etwa 700 Menschen starben und etwa 40.000 flohen aus Angst vor Repressalien in die benachbarten Länder Benin und Ghana. Dies sowie die anhaltende Aussetzung der Hilfeleistungen der EU trugen zur weiteren Verschlechterung der wirtschaftlichen Lage bei.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2005; domestic policy; Foreign affairs; socio-economic development; period under review 2005